2019
DOI: 10.24926/iip.v10i1.1347
|View full text |Cite
|
Sign up to set email alerts
|

Ohio Community Pharmacist Provision of Clinical Preventive Services

Abstract: Objective: The primary objective of this study was to assess whether Ohio community pharmacists currently provide certain evidence-based clinical preventive services.  Secondary objectives were to explore whether there were any differences in provision of services based on respondent education, position, employment status, location, practice setting, or years in practice and to gather information on how pharmacists provide specific services, barriers to providing specific services, pharmacists’ perceptions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Detailed information regarding respondents' direct provision of clinical preventive services that can be provided in a community pharmacy has already been reported. 9 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information regarding respondents' direct provision of clinical preventive services that can be provided in a community pharmacy has already been reported. 9 …”
Section: Resultsmentioning
confidence: 99%
“…Detailed information regarding respondents' direct provision of clinical preventive services that can be provided in a community pharmacy has already been reported. 9 In regards to community-clinical linkages, 16 (17%) of respondents indicated that they currently partner with a prescriber who refers patients to their community pharmacy for assistance with medications or chronic disease state management. Community pharmacists at urban locations reported such relationships more often than those at suburban or rural locations (p=0.022); there was no significant difference seen by education (p=0.316).…”
Section: Resultsmentioning
confidence: 99%